PERSONALITY OF THE CHARACTER "I" IN THE SHORT STORY "OREZ" BY BUDI DHARMA: LITERARY PSYCHOLOGY STUDY - Ramadhanti, Nella Viana Nur; Indriyani, Jiphie Gilia; Moh. Atikurrahman (Prologue: Journal on Language and Literature, 2024)
This research aims to describe the psychological aspects of personality experienced by the character "I" in the short story "Orez" in the short story Orang-Orang Bloomington by Budi Darma which describes fear and awareness. The research method used is a qualitative descriptive method. The technique used in this research is the technique of reading and taking notes from the short story "Orez", a collection of Bloomington People's short stories. The researcher read the short story "Orez", a collection of Bloomington People's short stories, then recorded data that included the psychological aspects of the character "I". The data taken in this research is through paragraphs of the short story "Orez" Orang-Orang Bloomington by Budi Drama. This research uses Sigmund Freud's theory which consists of the elements Id, ego and super ego. The interesting object of the research update is that this research reveals the psychology of the parents of the character "I" (Orez's father). The results of this research are a description of the psychological personality side of Id, ego and super ego experienced by my character in the short story "Orez" in the short story collection Orang-Orang Bloomington by Budi Darma.